Performance Investigation of a Vertical Wave-plate Mist Eliminator with Perforated Plates - Seung-Yoon Noh; Moon-Won Kim; Se-Jin Yook (Aerosol and Air Quality Research)
Abstract This study improved collection efficiency of the mist eliminator used for wet flue gas desulfurization facilities. The commonly used wave-plate mist eliminator with a drainage channel was chosen as a reference model and its performance was compared with the performance of a wave-plate mist eliminator with perforated plates attached to the front of each drainage channel. Simulations were performed to compare the dust collection performance of the mist eliminators. We could confirm that the addition of perforated plates to the mist eliminator changed the particle behavior in front of the drainage channel and induced the passage of particles through the mist eliminator and into the drainage channel. Subsequent experiments confirmed that dust collection performance was improved with the use of the perforated plates. The use of the mist eliminator designed in this study is expected to greatly reduce the amount of air pollutants emitted from various industrial facilities.